Short-term evaluation of tegumentary changes of the nose in oral breathers undergoing rapid maxillary expansion - Badreddine,Fauze Ramez (2018)
Abstract Introduction Rapid maxillary expansion is an orthodontic and orthopedic procedure that can change the form and function of the nose. The soft tissue of the nose and its changes can influence the esthetics and the stability of the results obtained by this procedure. Objective The objective of this study was to assess the changes in nose dimensions after rapid maxillary expansion in oral breathers with maxillary atresia, using a reliable and reproducible methodology through computed tomography. Methods A total of 30 mouth-breathing patients with maxillary atresia were analyzed and divided into a treatment group who underwent rapid maxillary expansion (20 patients, 10 of which were male and 10 female, with a MA of 8.9 years and a SD of 2.16, ranging from 6.5 to 12.5 years) and a Control Group (10 patients, 5 of which were male and 5 female, with a MA of 9.2 years, SD of 2.17, ranging from 6.11 to 13.7 years). In the treatment group, multislice computed tomography scans were obtained at the start of the treatment (T1) and 3 months after expansion (T2). The patients of the control group were submitted to the same exams at the same intervals of time. Four variables related to soft tissue structures of the nose were analyzed (alar base width, alar width, height of soft tissue of the nose and length of soft tissue of the nose), and the outcomes between T1 and T2 were compared using Osirix MD software. Results In the TG, the soft tissues of the nose exhibited significant increases in all variables studied (p < 0.05), whereas, changes did not occur in the control group (p > 0.05). In the treatment group, mean alar base width increased by 4.87% (p = 0.004), mean alar width increased by 4.04% (p = 0.004), mean height of the soft tissues of the nose increased by 4.84% (p = 0.003) and mean length of the soft tissues of the nose increased by 4.29% (p = 0.012). Conclusion In short-term, rapid maxillary expansion provided a statistically significant increase in the dimensions of the soft tissues of the nose.